GAMBARAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEKAMBUHAN KLIEN GANGGUAN JIWA DI RUMAH SAKIT KHUSUS DAERAH PROVINSI SULAWESI SELATAN - haikal alpin; Nur febrianti; Efendi (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
Mental disorders are one of the four major health problems in developed, modern and industrialized countries. The four main problems are degenerative diseases, cancer, mental disorders, and accidents. Symptoms of mental disorders, especially schizophrenia, are divided into two main categories, namely positive symptoms or real symptoms, including: delusions, hallucinations, disorganized thoughts, speech and disorganized behavior. Mental relapse is a client's condition where the same symptoms appear as before and result in the client having to be treated again. This study aims to determine the description of the factors that influence the recurrence of clients with mental disorders. The research design used in this study is descriptive. The data used in this study are primary data and secondary data where the primary data is obtained directly from the families of mental patients who are hospitalized in the hospital by using a questionnaire and for secondary data is obtained directly by looking at the visiting data of patients with mental disorders who are hospitalized in the hospital. The number of samples in this study amounted to 30 people taken from the total population as a whole. The results of this study indicated that there were 24 respondents (80.0%) who had support from (good) families and 6 respondents (20.0%) who lacked. Respondents social environment support: good 20 respondents (66.7%) less as many as 10 respondents (33.3%) while the regularity of taking medication: it can be seen that 9 respondents (30.0%) are lacking while 21 respondents (70.0%) are good. It is recommended for families to be able to provide support for patients both in the form of moral, material, spiritual support to prevent and minimize the occurrence of recurrence in clients with mental disorders